The influence of tracking marker locations on three-dimensional wrist kinematics - Turner, J.; Forrester, S. E.; Mears, A. C.; Roberts, J. R. (Journal of Science and Medicine in Sport, 2020)
Objectives: To determine the influence of tracking marker locations on wrist kinematics during free movements and the golf swing, with the intention of recommending a solution that generates meaningful three-dimensional wrist kinematics. Design: Repeated measures. Methods: Six participants performed free movements of flexion/extension, radial/ulnar deviation and forearm supination/pronation, with a further sixteen participants performing golf drives. A passive motion capture system tracked four different marker sets located on participants` hand and forearm segments. Variables of peak angle and range of motion were used to compare marker sets during free movements and angles at the top of the backswing and impact were compared during the golf swing. Results: Wrist marker set had a large (n2=0.557) and often significant (p=0.051) effect on the variables measured during free movements, and a mixed (n2=0.108, p=0.198) effect on wrist angles during the golf swing. Wrist axial rotation range of motion during free forearm supination/pronation revealed the greatest difference between marker sets (~42°). The large values generated by two of the marker sets for this rotation appeared to influence the values of flexion/extension and radial/ulnar deviation during the golf swing. Conclusions: The location of markers used to measure wrist kinematics can have a large effect on the angles generated. A solution of two markers located at the distal end of the forearm and one at the proximal, appears to minimise values of wrist axial rotation during free forearm supination/pronation and, consequently, produce more meaningful three-dimensional wrist kinematics.